Studi Implementasi Flight Information Display System (FIDS) di Bandar Udara Tjilik Riwut Palangkaraya - Shelly Meilani (Jurnal Multidisiplin Madani, 2022)
The Flight Information display system (FIDS) in the current digital era is very helpful for all visitors who are at the airport terminal, so that the use of FIDS displayed must be with complete information data in order to prevent flight information mistake. The research is a qualitative descriptive type. The data collection methods in this study are interviews, documentation, observation, and literature study. The purpose of this study was to find out how the implementation of FIDS, what obstacles were experienced by the information unit officers, and how the officer handled obstacles in the implementation of FIDS. Based on the results of research when use FIDS at the airport, it can be accessed online or offline with real time flight time data, so that this can minimize incorrect information displayed on the FIDS system.